Implementation of Learning Management, Exploring Weaknesses and Strengths: A Case Study - Nana Suryapermana; Moch Subekhan; Moch Abdul Rohman (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2022)
This study aims to analyze learning management, the strengths and weaknesses of the learning process, and student interest in learning. The research was conducted at Sirojul Atfal Cisoka High School. The research method uses descriptive qualitative and collecting data using observation, interviews, and documentation. The results showed that learning management was implemented through three stages: planning, implementation, and evaluation of learning. The integration of general subjects with religious subjects is an advantage of the learning process. However, the learning process that has not been appropriately managed makes it a weakness. This weakness causes students' low interest in learning, so their learning achievement decreases drastically.